Foreign Direct Investment in Sudan - Salih, Yasir (2012)
Due to the change in the world and rapid growth in the development of the countries, most of the developing countries try to make a full use of their resources: natural, human…etc. and to make this happen they move to attract the foreign direct investment from the other country who have the capabilities to help them and invest on the sectors that need development. In this research we focus in how the Sudan Government try to attract the FDI to develop the agriculture sector and try to avoid the loss of the oil by increase the contribute in the GDP, and what policies they use to do that, and how they use their natural resources to attract the investors. Also, we see what benefit the government expect from the FDI, also see what make the foreign investors to came and invest in Sudan, what benefit they get from this investment. Also, to know how the local investors see the foreign direct investment help the agriculture sector and is it really developing.